Problematika Pembelajaran Akidah Akhlak di MTsN 4 Lima Puluh Kota - M Afdhal Lizikri; Muhiddinur Kamal; Arifmiboy Arifmiboy; Afrinaldi Afrinaldi (Lembaga Pengembangan Kinerja Dosen, 2023)
In the learning process there will definitely be problems, both problems from the delivery of material by the teacher, problems from students, or inadequate facilities. There are many problems in learning the moral creed at MTsN 4 Fifty Cities, starting from a lack of enthusiasm for learning the moral creed. There are still students who are less active, feel bored in participating in the learning process and do not pay attention to what is conveyed by the teacher, children are indifferent to the assignments and notes given. This research is a descriptive qualitative research, the data collected is in the form of words, in this case it is explaining the problems of learning aqidah morals. Researchers collected data through interviews, documentation, and field notes. Data were analyzed in three stages, namely data reduction, data presentation, and data verification. Techniques for guaranteeing the validity of the data are source triangulation, technical triangulation, and time triangulation. Based on the results of the research that the researchers conducted, it can be concluded that: (1) The learning process of Aqidah Akhlak at MTsN 4 Fifty Kota is still in the development stage and is trying to achieve the best. By providing facilities and infrastructure to support the learning of aqidah morals, (2) The problems of learning Akidah Akhlak Class 7 at MTsN 4 Fifty Kota can be seen from two factors, namely, first, internal factors, namely problems that generally occur in teachers and students. The problem of the teacher's aqidah morals is how to convince children of the unseen and convince them to adhere to true Islamic beliefs, from students, namely they often don't focus when studying, feel bored, sleepy in class. Problems from external factors, namely the incompatibility between learning materials of the moral creed and its application in the school, family and community environment. (3) In overcoming problems related to internal factors, namely the efforts made by the teacher to overcome these problems by continuing to improve competence, MGMP activities, continuing to actively communicate with students.